Effect of irrigation needle depth in smear layer removal: Scanning electron microscope study - Ayman Mandorah (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate the cleanliness of rotary prepared root canals when the irrigation needle was placed at full or half the working length. Materials and Methods: Forty-five root canals were collected from extracted human teeth and divided into three groups each group of fifteen roots. Group 1: Root canals were instrumented using Profile® system and irrigated with 3% EDTA and 0.5% NaOCl. Group 2: Root canals were instrumented in the same manner as group 1 and irrigated with 18% EDTA and 5.25% NaOCl and the tip of the irrigation needle was introduced to the full working length. Group 3: Root canals were instrumented in the same manner as group 2 except that the tip of the irrigation needle was introduced half the working length. The roots were sectioned longitudinally and evaluated for smear layer at coronal, middle and apical thirds of the canals under SEM. The results were analyzed using the Kruskal-Wallis test. Results: No statistically significant difference was found in the distribution of the scores between all groups. However, the scores in the apical part of group 1were significantly higher than the middle and the coronal areas. Conclusion: The placement depth of irrigation needle or concentration of irrigants solutions has no influence on the cleanliness of rotary prepared canals.